2018
DOI: 10.5937/jouproman6-16650
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the adoption of e-tilang: Empirical evidence from the UTAUT model

Abstract: Mid-year 2017 The National Police of the Republic of Indonesia publishes e-tilang technology innovation. Traffic police use e-tilang in handling vehicles that violate traffic on the highway. This is to improve service to the public. This research factor influences acceptance and use of e-tilang by using UTAUT model. This research was conducted in Bengkulu area with 152 traffic policemen. The findings of this study indicate that effort expectancy, performance expectancy, and social influences positively affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Also, efforts were found to be more prominent in women than men [16] whereas previous studies have found that men are more schematic in processing information and relevant details tend to be ignored, while women tend to be piecemeal and detail in processing information so that it will weaken the effects of habits on intention or behaviour [17]. The extent to which people believe using SIMPEG will provide increased performance in their work [13]. Effort Expectancy (EE)…”
Section: Humanmentioning
confidence: 98%
“…Also, efforts were found to be more prominent in women than men [16] whereas previous studies have found that men are more schematic in processing information and relevant details tend to be ignored, while women tend to be piecemeal and detail in processing information so that it will weaken the effects of habits on intention or behaviour [17]. The extent to which people believe using SIMPEG will provide increased performance in their work [13]. Effort Expectancy (EE)…”
Section: Humanmentioning
confidence: 98%